Perinatal mental health module for nurses - Mohd Arifin, Siti Roshaidai; Muhammad, Noor Azimah; Musa, Ramli (2023)
In low- and middle-income countries, like Malaysia, as many as 1 in 5 new mothers experience some type of maternal mental health disorders including perinatal depression and anxiety. However, many cases remain under-detected and under-treated due to stigma and a lack of awareness on perinatal mental health. Nurses, especially those working in the primary care setting, are frequently meeting with antenatal mothers throughout their pregnancy course. However, they have a lack of professional development on education and skills related to perinatal mental health. This invited slot discusses on the perinatal mental health module for nurses to improve their care and management, reduce the stigmatization, increase awareness, avoid delay of care, identifying patient’s symptoms & assessment and build confidence and skills in assessing, supporting and referring mothers with perinatal mental disorders.